Implementasi Metode Triangle Geometry Untuk Pengenalan Arah Pergerakan Kepala - Irnayanti Dwi Kusuma; Fitri Utaminingrum; Randy Cahya Wihandika (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Nowadays, applications that detect head or face are popularly used as device securing, virtual and augmented reality, computer games, and device control. However, people with physical disabilities have constraints to control the system, on the other hand there are also constraints on normal users who use headpieces to control the system that is the cost allocation for headpiece purchases. Identification of head direction movement using Triangle Geometry Method could be implemented into a system that utilizes input as a control. Utilization of inputs as controls can make easier for people with disabilities to use a system and use it interactively. In addition, this topic can help reduce the cost of system requirements and does not complicate the user, such as using a special device that put on the user's head to control a system. Skin color detection, eyes, and nose are phases that used on this topic to build a system of face detection and head direction movement. This research focuses on the success of systems that can recognize the direction of head movement with the state of the head in real-time. The direction of the head is up, down, right and left. The system processes the value of yaw, pitch, roll with triangle geometry method so it can get a range values ​​for each direction of head movement. The accuracy value of each direction is 88% for the upward direction, 82.6% for the downward direction, 84.6% for the right direction and 73.5% for the left direction. So, this system can be implemented as control input.